2019
DOI: 10.1177/0960327119895564
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin protects the testis against cadmium-induced histopathological damages and oxidative stress in mice

Abstract: Background: Cadmium is an environmental pollutant which can induce the overproduction of free radicals while suppressing the antioxidant defense system. Curcumin is considered a free-radical scavenger and a potent antioxidant. This study was conducted to investigate the effect of curcumin on serum antioxidant enzymes and histopathological changes in mice treated with cadmium. Methods: In this experimental study, adult mice were divided into four groups, namely, control, cadmium chloride (5 mg kg−1), curcumin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 36 publications
0
16
1
Order By: Relevance
“…In these studies in the literature list, we have learned that cadmium causes decreased levels of the indicator related to testicular oxidation in the testicular tissue. 4,5,[7][8][9] In our current study, in cadmium chloride group, SOD and GPx activity and GSH and testosterone levels were significantly lower than the control group. Our results support the previous studies.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…In these studies in the literature list, we have learned that cadmium causes decreased levels of the indicator related to testicular oxidation in the testicular tissue. 4,5,[7][8][9] In our current study, in cadmium chloride group, SOD and GPx activity and GSH and testosterone levels were significantly lower than the control group. Our results support the previous studies.…”
Section: Discussioncontrasting
confidence: 38%
“…1 Cadmium, a heavy metal, has been reported to be abundant especially in industrial areas, 2 causing injury in the liver, kidneys and testicles. [3][4][5][6][7][8][9] Especially, in the toxicity it causes in the testicles, it has been reported that spermatogenesis is impaired and there are decreases in gonadotropic hormones and testosterone hormone. [10][11][12] It has also been reported to cause apoptosis in the male reproductive cell.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Cur, the main natural polyphenol found in the rhizome of Curcuma longa and in other Curcuma spp., showed protective effects against oxidative damage [ 29 ], as it inhibited the in vitro production of TNF-α [ 24 ] and scavenged ROS [ 25 ]. In Cd-treated rats, Cur administration improved the oxidative stress [ 27 ], partially protected seminiferous tubules morphology [ 26 ], and significantly decreased (but not to normal values) the number of apoptotic germinal cells [ 28 ]. In our study, Cur alone, particularly at 100 mg/kg, was able to increase the body and the testis weight to modulate the inflammatory and apoptotic pathways and to reduce the structural damages and the morphological parameters of the seminiferous tubules, thus playing a role in the treatment of human infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Cur, Re, and BJe were orally administered for 14 days, while CdCl 2 was dispensed intraperitoneally (i.p.). The doses of CdCl 2 as well as BJe, Re, and Cur employed in this study were chosen in agreement with previous findings [ 11 , 13 , 20 , 27 , 33 , 39 , 59 , 60 , 70 ]. Twenty-four hours after the last treatment, all mice were weighted and sacrificed with an overdose of ketamine and xylazine (75/10 mg/kg i.p.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation